Comparative Morphological Characteristics Of Uterine Diseases Identified By Ultrasound Examination - Shuhratovich, Usarov Muhriddin; Abdurakhmanovich, Khamidov Obid; Eshmamatovich, Jumanov Ziyodulla; Ibragimovich, Davranov Ismoil (Journal of Neonatal Surgery, 2025)
This article presents a comparative analysis of the morphological characteristics of uterine diseases identified through ultrasound examination and evaluates their clinical relevance and diagnostic value. The study includes a range of uterine pathologies such as fibroids (leiomyomas), adenomyosis, endometritis, and other structural abnormalities observed in patients of varying reproductive ages. Ultrasound (US) remains one of the most effective, non-invasive, and accessible diagnostic tools in gynecology. Its high sensitivity allows for the early detection of changes in uterine structure, even in asymptomatic patients. In this study, the echo graphic features of various uterine diseases were compared with their corresponding histopathological (morphological) findings obtained through biopsy, curettage, or surgical specimens. The specific ultrasound criteria and patterns for each pathology were described in detail to aid in differential diagnosis. For example, uterine fibroids were characterized by well-defined, hypoechoic masses with a homogeneous or heterogeneous internal structure, while adenomyosis typically showed a diffusely enlarged uterus with myometrial cysts and indistinct endometrial-myometrial borders. Endometritis was associated with an irregular endometrial lining and increased vascularity on Doppler imaging. The results of the study demonstrate that when ultrasound data are interpreted in conjunction with morphological analysis, the accuracy of diagnosis significantly improves. This integrated approach enhances clinical decision-making, enabling timely and appropriate treatment interventions. The paper concludes that sonographic examination, combined with histological assessment, remains essential for the comprehensive evaluation of uterine diseases.